Dynamic Behaviour of the Arch Bridge – The Full-Scale Testing - Milan Moravcik; Martin Moravcik (Communications - Scientific letters of the University of Zilina, 2011)
In the paper the full-scale dynamic testing procedure for highway bridges is presented. The procedure is applied on the new highway steel arch bridge in highway R1 at the locality Nitra – Selenec. After a general description of the bridge, some results relative to inspection and the spectral analysis are reported. The testing equipment, methods of evaluating and processing obtained records utilised during the forced vibration of the bridge are described.